AN OBSERVATIONAL STUDY ON PREDICTION OF DIFFICULTIES DURING LAPROSCOPIC CHOLECYSTECTOMY IN CASES OF CHOLELITHIASIS BY PREOPERATIVE ULTRASONOGRAPHY - Sanjay Kumawat; lakshman agarwal; Amit Yadav (Basrah Journal of Surgery, 2022)
INTRODUCTION: Acute appendicitis is one of the commonest causes of acute abdomen encountered in surgical practice, requiring emergency surgery. Open appendicectomy by Grid Iron incision had been gold standard for many years. Laparoscopic technique provided an opportunity to explore new method of management of the suspected cases of the acute appendicitis. AIMS & OBJECTIVES: To compare laparoscopic and open appendicectomy in terms of intra-operative duration, complication of surgery and post operative outcome. MATERIALS AND METHODS: A total of 50 patients with clinical diagnosis of appendicitis were studied. After pre-operative work up, patients were randomly assigned for laparoscopic appendicectomy or open appendicectomy. All cases were observed in the intra- and post-operative period till they were discharged and then later followed up for a period of 4 weeks in the outpatient department. OBSERVATIONS AND RESULTS: A total of 25 patients assigned for laparoscopic appendectomy and 25 patients assigned for open appendectomy were analysed. Majority of patients were male in 3rd or 4th decade of life and had acute appendicitis. There was statistically significant difference of duration of surgery, post-operative pain, duration of hospital stay and return to work in both the groups. There was statistically insignificant difference of post-operative complication in both the groups.